PROGRAM INKLUSI KEUANGAN SYARIAH UNTUK MENINGKATKAN KESEJAHTERAAN UMKM - Nasyiatul Farida; Moh. Arifin (LP2M IAI Miftahul Ulum Pamekasan, 2022)
Access to finance by MSMEs is still quite difficult, until a financial inclusion program appears whose goal is to make it easier for MSMEs to get financing. The program is driven by BMT as a sharia-based socio-economic institution whose aim is to improve the welfare of the community. This research is a qualitative type with a case study approach. The data were obtained through interviews, observations, and documentation which were analyzed using explanatory methods. The result of this study is that the financial inclusion program has been able to provide access for the unbanked community to obtain convenience in applying for financing. The concept of Islamic service excellent has been able to provide comfort and convenience for MSMEs to conduct financing transactions to develop their business. So that prosperity can be achieved by increasing income.